Reconfigurable transmissive metasurface synergizing dynamic and geometric phase for versatile polarization and wavefront manipulations. (January 2023) - Wang, Chaohui; Xu, He-Xiu; Wang, Yanzhao; Hu, Guangwei; Luo, Huiling; Wang, Kun
Graphical abstract: Highlights: The designed metasurface achieves high-rate transmission of 0.9. The designed metasurface successfully implements various functions between polarization-encoded channels at 7.4 GHz. The designed metasurface can manipulate transmitted waves with reconfigurable property by controlling direct current bias volt ages. The designed metasurface controls transmitted waves in two orthogonal linear polarization and circular polarization channels. Abstract: Recently, reconfigurable metasurfaces have facilitated dynamic manipulation of electromagnetic (EM) waves, opening new opportunities for fascinating meta-devices. So far, most devices are working in reflection region with limited polarization states. Here, we demonstrate a reconfigurable multifunctional transmissive metasurface for both linearly and circularly polarized waves manipulations. Specifically, the designed meta-atom contains dual-layer metallic cross-strips and one-layer circular slotted patch. Eight positive-intrinsic-negative diodes are loaded between each strip structure through via hole, with each two of diodes as a group along x - and y -direction, respectively, and thus supporting four switchable states via different applied bias voltages. Numerical results indicate that the designed meta-atom achieves high-rate transmission of 0.9 and individual phase manipulation in four independent transmission channels at 7.4 GHz. As a proof-of-concept demonstration, we numerically and experimentally show different versatile functionalities, including anomalous deflections with steered beams in range of 0° ∼ 40°, orbital angular momentum generation with mode of l  = 1, and beam focusing among four polarization-encoded channels at 7.4 GHz. Our metasurface owns the advantages of multi-polarization EM wave manipulations in transmission mode, which completely distinguishes from previously reported works with single polarization in reflection mode.